The Effect of Learning Interest and Learning Environment on Student Learning Outcomes in History Class X IPS - Linda Wati; Salsabila Afifah (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: To determine the effect of interest and the learning environment on student learning outcomes in sijarah subject class X IPS SMA N 1 Sungai Penuh. Methodology: This research includes quantitative research with descriptive methods. sampling using saturated sample technique. Data on interest in learning and the learning environment were collected through questionnaires, while data on student learning outcomes was obtained through documentation, namely odd semester exam scores. Data analysis techniques in this study used descriptive analysis techniques and regression analysis. Main Findings: There is a joint effect of interest in learning and the learning environment on student learning outcomes in class X IPS at SMA Negeri 1 Sungai Full with the coefficient of regression field equation variable interest in learning 0.671 and learning environment variable 0.420. Novelty/Originality of this study: This study discusses 2 variables in determining learning outcomes, namely using interest and learning environment variables.